1997
DOI: 10.1038/nbt0897-778
|View full text |Cite
|
Sign up to set email alerts
|

Solid stress inhibits the growth of multicellular tumor spheroids

Abstract: In normal tissues, the processes of growth, remodeling, and morphogenesis are tightly regulated by the stress field; conversely, stress may be generated by these processes. We demonstrate that solid stress inhibits tumor growth in vitro, regardless of host species, tissue of origin, or differentiation state. The inhibiting stress for multicellular tumor spheroid growth in agarose matrices was 45 to 120 mm Hg. This stress, which greatly exceeds blood pressure in tumor vessels, is sufficient to induce the collap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

73
736
6
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 759 publications
(819 citation statements)
references
References 28 publications
73
736
6
4
Order By: Relevance
“…In 1.8% agarose gels the growth is completely arrested. We suggest that this inhibition in growth results from increasing stress as trapped spheroids grow within denser gels, consistent with our previous data on five different cell lines: LS174T (human colon adenocarExperimental Therapeutics cinoma), MCaIV (murine mammary carcinoma), and the clones (A, B, C) of a rat rhabdomyosarcoma, BA-HAN-1 (Helmlinger et al, 1997a). Unlike our previous study, we found that the specific growth rate, a, decreased with increasing gel concentration for AT2.1 (P=0.023), but not for AT3.1 ( Figure 2C).…”
Section: Solid Stress Inhibits Spheroid Growthsupporting
confidence: 91%
See 2 more Smart Citations
“…In 1.8% agarose gels the growth is completely arrested. We suggest that this inhibition in growth results from increasing stress as trapped spheroids grow within denser gels, consistent with our previous data on five different cell lines: LS174T (human colon adenocarExperimental Therapeutics cinoma), MCaIV (murine mammary carcinoma), and the clones (A, B, C) of a rat rhabdomyosarcoma, BA-HAN-1 (Helmlinger et al, 1997a). Unlike our previous study, we found that the specific growth rate, a, decreased with increasing gel concentration for AT2.1 (P=0.023), but not for AT3.1 ( Figure 2C).…”
Section: Solid Stress Inhibits Spheroid Growthsupporting
confidence: 91%
“…Similar to our previous findings (Helmlinger et al, 1997a), the AT2.1 spheroids retained their morphology and resumed their growth as in free suspension (Figure 3). The AT3.1 cells also retained their morphology for the first several days, but lost their integrity by days 6 -8 and disintegrated into a loose collection of cells.…”
Section: Relieving Stress Causes Loss Of Spheroid Integritysupporting
confidence: 90%
See 1 more Smart Citation
“…Once the space is filled near the origin of TECs, TECs begin to feel a reciprocal tissue resistance force from the surrounding stromal tissue and tend to grow in the longitudinal direction, i.e., in the direction of less stress. This is qualitatively consistent with experimental results described earlier on anisotropic growth (Helmlinger et al 1997;Cheng et al 2009). Figure 20(H) shows the time course of the tumor population for both cases in (F) and (G) above.…”
Section: The Effect Of the Stiffness Of The Stromal Tissuesupporting
confidence: 90%
“…Parameter PRCC\ k Parameter PRCC\ k other tumor types that the surrounding medium affects growth of tumor spheroids (Helmlinger et al 1997;Cheng et al 2009). Transformed mammary epithelial cells may also respond to stresses by increasing FGF and VEGF signaling to promote their proliferation and by increasing production of MMPs to promote invasion (Paszek and Weaver 2004).…”
Section: The Mathematical Model For Tumor Growth In a Ductmentioning
confidence: 99%